Sistem Informasi Geografis Persebaran Nasabah Pt Pegadaian Persero Cabang Mengwi Berbasis Web - Sudiawan, Kadek Agus (JUSS (Jurnal Sains dan Sistem Informasi), 2025)
Current technological developments can be said to grow faster. The developments that occur also occur in various sectors such as education, industry and even to the field of mapping. PT Pegadaian encountered problems if there were customers who had been bogged down because the information process distributed to employees was still conventional and not yet integrated. To overcome these problems, the design of Geographic Information System for Customer Distribution of PT Pegadaian Persero Cabang Mengwi is made. The design of the application made there are several features such as managing customer data, managing customer credit, viewing the customer's location on the map, viewing reports for the leadership and several other supporting features. After that, an analysis of the information system is designed to determine the level of effectiveness, after the system is designed and analyzed for effectiveness, the result is a system that is designed to have a "Very Good" effectiveness with an interpretation of 81.38% so that the system can be implemented and able resolve problems that exist in PT. Pegadaian Persero Branch Mengwi.